An international analysis of earnings, stock prices and bond yields - Alain Durré; Pierre Giot (European Central Bank (ECB), 2005)
This paper assesses the possible contemporaneous relationship between stock index prices, earnings and long-term government bond yields for a large number of countries and over a time period that spans several decades. In a cointegration framework, our analysis looks at three hypotheses. First, is there a long-term contemporaneous relationship between earnings, stock prices and government bond yields? Second, does a deviation from this possible long-run equilibrium impact stock prices such that the equilibrium is restored? Third, do government bond yields play a significant role in the long-run relationship or does the latter only involve stock prices and earnings? We also study the short-term impact of changes in long-term government bond yields on stock prices and discuss our short-term and long-term results in light of the recent developments regarding the so-called Fed model.
Keywords: C13; C22; F31; G14; 330; earnings; inflation; Interest Rates; long-run relationships; market valuation; stock indexes; Aktienindex; Rendite; Lohn; Schätzung; VAR-Modell; OECD-Staaten